2023
DOI: 10.1007/s10797-023-09791-z
|View full text |Cite
|
Sign up to set email alerts
|

Government debt, European Institutions and fiscal rules: a synthetic control approach

Abstract: Public debt and its development are key questions of public sector economics and fiscal policy. This paper uses the Synthetic Control Method to study how different large-scale steps of European integration and the establishment of the EU fiscal framework have affected government debt in EU Member States. The results point to a notable debt-restricting effect of EU membership and the introduction of the Stability and Growth Pact for a large majority of the studied country groupings as well as for individual cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A more comprehensive look at determinants of government debt and how different dynamics affect the process as well as more detailed reasons, and whether effects are heterogenous for different countries, could be an avenue for future research. Another potential way forward would be a more granular look at how different forms of national fiscal rules for different sectors can affect government debt growth, or by using novel econometric methods to study how the introduction of specific fiscal rules or reforms has affected the development of government debt as done for the formation of the EU and the establishment of the SGP in Kraemer and Lehtimäki (2023). It might also be beneficial to study other indicators of government debt and fiscal status as identified in Bloch and Fall (2016) to better understand different facets of public sector debt sustainability.…”
Section: Appendix 1: Data Description and Sourcesmentioning
confidence: 99%
“…A more comprehensive look at determinants of government debt and how different dynamics affect the process as well as more detailed reasons, and whether effects are heterogenous for different countries, could be an avenue for future research. Another potential way forward would be a more granular look at how different forms of national fiscal rules for different sectors can affect government debt growth, or by using novel econometric methods to study how the introduction of specific fiscal rules or reforms has affected the development of government debt as done for the formation of the EU and the establishment of the SGP in Kraemer and Lehtimäki (2023). It might also be beneficial to study other indicators of government debt and fiscal status as identified in Bloch and Fall (2016) to better understand different facets of public sector debt sustainability.…”
Section: Appendix 1: Data Description and Sourcesmentioning
confidence: 99%